(untitled) (Biological Sciences - PJSIR, 2022)
The study dealt with the helminthic fauna infecting Black-winged stilt, Himantopus himantopus (L.) (Charadriiformes, Recurvirostridae) from Sindh, Pakistan, includes the investigation of new varieties of helminths in wader birds of Sindh and the assessment of prevalence and the rate of infection in Black- winged Stilt, during August-November 2018. A total of 12 birds were captured from various areas of Sindh province, in which 9 birds were found infected with helminthes with total prevalence and the rate of infection were found 75% and 0.77, respectively. At present, cestodes Himantocestus giganticus, Infula burhini, Diplophallus andinus and a female nematode of Amidostomum species were recovered, with species wise prevalence and rate of parasitic infection were calculated for D. andinus 80% and 2, respectively for H. giganticus 77.77% and 2.285 for Infula burhini 100% and 2 and for Amidostomum species 80% and 3, respectively. Dipolophallus andinus was first time reported in the present host, while more investigation for nematodes is required.